2013
DOI: 10.1074/mcp.m112.027136
|View full text |Cite
|
Sign up to set email alerts
|

Dermatophagoides farinae Allergens Diversity Identification by Proteomics

Abstract: The most important indoor allergens for humans are house dust mites (HDM). Fourteen Dermatophagoides farinae allergens (Der f 1-3, 6, 7, 10, 11, 13-18, and 22) are reported although more than 30 allergens have been estimated in D. farinae. Seventeen allergens belonging to 12 different groups were identified by a procedure of proteomics combined with two-dimensional immunoblotting from D. farina extracts. Their sequences were determined by Edman degradation, mass spectrometry analysis, and cDNA cloning. Their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 36 publications
5
61
0
Order By: Relevance
“…32. These results clearly demonstrate that K 50 , and not T 53 or T 67 , is modified by Hex. Similar results were obtained for the Der f 2 allergen.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…32. These results clearly demonstrate that K 50 , and not T 53 or T 67 , is modified by Hex. Similar results were obtained for the Der f 2 allergen.…”
Section: Resultssupporting
confidence: 52%
“…S8 and S9) both T 53 and T 67 , was observed without Hex modification at m/z 1595.79. In addition, the c4 fragment, which excludes both T 53 and T 67 but includes K 50 , was observed with a 162.05 amu mass increment, corresponding to a Hex residue, at m/z 609. 32.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…71 The IgE responses have yet to be quantitated or compared with other allergens. 72 Allergenicity was further examined with chromatographically isolated proteins although the profiles show a requirement for further purification and then quantitation and the exclusion of cross-reactive carbohydrate binding. Little IgE binding to myosin alkali light-chain protein, pyrophosphatase and ferritin has been found to recombinant proteins 71,73 in other studies and ferritin has been found not to induce Th2-biased cytokine responses.…”
Section: Group 22 Allergensmentioning
confidence: 99%
“…Detection of cross-reactive pollen allergens: Previously, proteins of GST-family were identified as allergens in house dust mite allergen, Der 20 and German cockroach, Bla g5 21 . We investigated a potential cross-reactivity between GST from birch and GST from parthenium.…”
Section: Fig2: Gst Antibodies Raised Towards the Vt20 And Bet V1 Polmentioning
confidence: 99%